Single-phase high-voltage gain switched LC Z-source inverters - Bussa V.K.; Ahmad A.; Singh R.K.; Mahanty R. (My University, 2025)
Recently, switched-inductor Z-source inverters (SL-ZSIs) have been reported to achieve high-voltage gain and good power inversion operation at low shoot-through duty ratio D as compared to conventional ZSI. As the SL-ZSIs have high passive component count, weight, volume and losses of the system increases that lead to reduction in efficiency. To address the issues of conventional ZSI and SL-ZSIs, two single-phase switched LC (SLC)-ZSIs (Type 1 SLC-ZSI and Type 2 SLC-ZSI) are proposed in this study to achieve high-voltage gains at low values of D with lower passive component count as compared to SLZSIs. At low values of D, modulation index M approaches to higher values which results into improved AC output at reduced harmonic distortion. Due to low passive component count in the proposed inverters, weight, volume and losses decreases resulting into increase in efficiency. The proposed inverters can be used in various DC-AC and DC-DC power conversions in renewable energy applications due to their high-voltage gain, better immunity to EMI noise and higher reliability. The detailed steady-state analysis of the two proposed SLC-ZSIs is given in this study. Scaled down experimentation has been carried out to verify the performance of the proposed inverters. © 2018, The Institution of Engineering and Technology.